PERAN KONSELOR DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA DI SMPN 2 BUKITTINGGI - Riska Nurjannah; Yeni Afrida; Yuniarti Yuniarti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Confidence is a deep belief that a person has about all the abilities he has and is aware of his shortcomings and is able to do something useful for himself and others. This study aims to find out how the role of the counselor in increasing the confidence of students of SMP Negeri 2 Bukittinggi in carrying out the learning process and in students' daily behavior. This research uses a qualitative approach with a descriptive method. The variables used are Student Confidence and the Counselor's Role. The technique used is non-test instrumentation in the form of interviews and observations. The key informants are counselors and student support informants. The results show that most of the students at SMPN 2 Bukittinggi are able to develop their self-confidence as best they can, such as being able to ask questions when they don't understand something and even being able to display their talents and interests according to the field at the school, but sometimes there are also students who are shy and are afraid to ask about something they don't know, the counselor's role here is to provide solutions for students who are unable to develop themselves properly to be able to develop the potential and problems students face everyday. It turns out that not only that, but students also use a lot of self-confidence in terms of doing bad things, which means that students use too much time just for promiscuity, so this can trigger students' self-confidence during the learning process. Not spared from the increasingly sophisticated technology used, most students use it in terms of seeking entertainment and being narcissistic in cyberspace so that this can result in low student motivation during the learning process.